Internal mechanisms of plant adaptation to aluminum toxicity and phosphorus starvation in three tropical forages - Watanabe, Toshihiro; Osaki, Mitsuru; Yano, Hiromi; Rao, Idupulapati M. (Informa UK Limited, 2006)
Many tropical forage grasses and legumes grow well in acid soils, adapting to excess aluminum (Al) and phosphorus (P) starvation stresses by using mechanisms that are still unclear. To determine these mechanisms, responses to Al toxicity and P starvation in three tropical forages were studied: two grasses, Brachiaria hybrid cv. ‘Mulato’ (B. ruziziensis clone 44-06 × B. brizantha cv. ‘Marandú’) and Andropogon gayanus, and one legume, Arachis pintoi. The tropical grasses tolerated high levels of Al toxicity and P starvation, with the Brachiaria hybrid maintaining very low levels of Al concentration in shoots. 27Al Nuclear Magnetic Resonance spectroscopy (NMR) analysis revealed that, in the Brachiaria hybrid, Al makes complexes with some ligands such as organic-acid anions in the root symplast. The forages probably adapted to P starvation through high P-use efficiency. These experiments provide the first direct evidence we know of that organic acid anions within root tissue help detoxify Al in non-accumulator species such as the Brachiaria hybrid.